1984
DOI: 10.1007/bf00262218
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and neurophysiological studies with the aldose reductase inhibitor, sorbinil, in symptomatic diabetic neuropathy

Abstract: Summary. The effect of sorbinil (200 mg daily for 4 weeks) was examined in 13patients, mean age 59.7years (range 42-72 years), with symptomatic diabetic neuropathy of mean duration 6years (range 1-18years). In this double-blind, placebo-controlled crossover trial, studies were made of motor, sensory and autonomic nerve function, severity of painful symptoms and duration of sleep. One patient was withdrawn because of an adverse reaction to sorbinil. In the other 12, constant mean values for glycosylated haemogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…We observed no effect of ponalrestat on autonomic nerve function, and this result is consistent with previous studies (10)(11)(12). There are several reasons why ponalr- Values are means ± SD.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We observed no effect of ponalrestat on autonomic nerve function, and this result is consistent with previous studies (10)(11)(12). There are several reasons why ponalr- Values are means ± SD.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, many studies in animals support the hypothesis that polyol pathway activation by hyperglycemia might cause nerve damage (7). The aldose reductase inhibitor class of drugs have been shown to prevent nerve damage in diabetic animals (7), but in humans, results of clinical trials with these drugs in diabetic autonomic neuropathy have been disappointing and have produced, at best, only slight treatment effects (8,9) or none at all (10)(11)(12). There have been no reported clinical trials in which the effects of aldose reductase inhibitor drugs on neutrophil function were assessed.…”
mentioning
confidence: 99%
“…Short-term trials with improvement (reversal) of diabetic neuropathy as the objective and with either a parallel-controlled or a crossover design constitute the majority of the previous studies (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)24,26,28,29,35). Two long-term trials with the objective of slowing progression with a parallel-controlled design have been completed (36,43).…”
Section: Clinical Trialsmentioning
confidence: 98%
“…Despite numerous trials of various aldose reductase inhibitors, none have been shown to prevent neuropathy or the progression of deficits. 11,102104 …”
Section: Types Of Diabetic Neuropathiesmentioning
confidence: 99%